Фертильность пыльцевых зерен и гибридизация картофеля (Solanum tuberosum L.) в условиях Таджикистана - Партоев, К.; Наимов, С.; Меликов, К.; Джумахмадов, А.; Абдурахимов, С. (Фактори експериментальної еволюції організмів, 2010)
In the conditions of a mountain zone of republic Tajikistan for the first time are spent studying fertility of pollen grains and hybridization varieties and clones of potato. Degree fertility pollen grains and the big variability of the given genetic sign among samples of potato (5–97%) is defined. It is established, that some clones of a potato have big variability to signs coloring flowers, pollens and forms stigma of flower columns. 10 clones of a potato with a sign of man’s sterility and smaller quantity fertility pollen grains (5,1–9,7%) are allocated. Such clones can serve as good stuff for breeder - genetic works on deducing of new hybrids and potato grades. Among grown up varieties of a potato the least quantity fertile pollen grains is observed at a grade the Cardinal (26,5%) and the greatest quantity fertile pollen grains at a perspective grade of a potato — Dusti (95,2%). As a result of the spent crossing of varieties and hybrids of potato received hybrid berries, seeds from which will be growing and studied in 2010.